Structural basis for Ragulator functioning as a scaffold in membrane-anchoring of Rag GTPases and mTORC1 - Tianlong Zhang (Nature Portfolio, 2017)
Activated Rag GTPases recruit mTORC1 to lysosomes. Here the authors present the crystal structure of the Ragulator complex and identify the binding sites for the Roadblock domains of Rag GTPases, which gives insights how Rag GTPases are tethered to the lysosomal membrane.